2022
DOI: 10.1186/s12886-021-02230-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aerobic exercise on tear secretion and tear film stability in dry eye patients

Abstract: Background To study the effects of aerobic exercise (AE) on tear secretion and tear film stability in dry eye patients. Methods This study consisted of two parts, each part included 3 groups, namely dry eye without AE group, dry eye with AE group and pre-clinical dry eye with AE group. In part 1, we studied the variations of Schirmer I test and six tear compositions before and after AE (34 eyes in each group). In part 2, we studied the variations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…A prospective cross-sectional study involving 43 healthy participants found significant reductions in tear fluid levels of inflammation-related cytokine, including interferon-γ (IFN-γ), tumor necrosis factor-α (TNF-α), interleukin (IL)-1β, IL-4, IL-5, and dozens of others, after a 20 min exercise session in comparison to the baseline levels (38). More excitingly, exercise reduced the tear fluid concentration of the marker of oxidative stress, 8-hydroxy-2′-deoxyguanosine (8-OHdG), suggesting that exercise may play a role in alleviating DED by reducing the oxidative stress present in tears (39) (see Table 1).…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…A prospective cross-sectional study involving 43 healthy participants found significant reductions in tear fluid levels of inflammation-related cytokine, including interferon-γ (IFN-γ), tumor necrosis factor-α (TNF-α), interleukin (IL)-1β, IL-4, IL-5, and dozens of others, after a 20 min exercise session in comparison to the baseline levels (38). More excitingly, exercise reduced the tear fluid concentration of the marker of oxidative stress, 8-hydroxy-2′-deoxyguanosine (8-OHdG), suggesting that exercise may play a role in alleviating DED by reducing the oxidative stress present in tears (39) (see Table 1).…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…to promote tear secretion and improves tear lm stability in dry eye patients, 50,53 and tear lm instability has been linked to LWE. 28 Other studies have also demonstrated a link between a lack of exercise (i.e., sedentary lifestyle) and risk of DE.…”
Section: Discussionmentioning
confidence: 99%
“…Sedentary behavior has been associated with reduced tear breakup time, lower tear volume, and risk of DE. [50][51][52][53] It has been speculated that exercise increases parasympathetic stimulation of the lacrimal gland and acinar blood vessels, increasing secretion of electrolytes and aqueous. 1 Approximately 2.5 hours more per week spent outdoors was found to be a heavily weighted predictor of lesser corneal staining extent, and of lower CLDEQ-8 score among contact lens wearers.…”
Section: Discussionmentioning
confidence: 99%
“…The Mediterranean diet has also been shown to be beneficial in systemic metabolic diseases and cardiovascular disorders [ 38 ]. It has also been confirmed that aerobic exercise promotes tear production and improves tear film stability in patients with DED [ 39 ]. Determining whether the prevention and control of diseases can be achieved through rational improvement of dietary patterns and healthy lifestyles is therefore significant and deserves long-term studies.…”
Section: Discussionmentioning
confidence: 99%